"Dis-able bodied" or "dis-able minded": stakeholders' return-to-work experiences compared between physical and mental health conditions. Issue 10 (8th May 2017) - Vossen, Emmie; Van Gestel, Nicolette; Van der Heijden, Beatrice I. J. M.; Rouwette, Etiënne A. J. A.
Abstract: Purpose: This study aimed to explore if and why the return-to-work (RTW) experiences of various workplace stakeholders in the Netherlands and Denmark differ between physical and mental health conditions, and to understand the consequences of potentially different experiences for the RTW process in both health conditions. Methods: We studied 21 cases of long-term sickness absence, and held a total of 61 semi-structured interviews with the various actors involved in these cases. Results: Physical cases were seen as "easy" and mental cases as "difficult" to manage, based on the visibility and predictability of health complaints. On this ground, assessing work ability and following required RTW actions were perceived as more urgent in mental than in physical cases. Despite these perceptions, in practice, the assessment of work ability seemed to impair the RTW process in mental cases (but not in physical ones), and the (non-)uptake of RTW actions appeared to have similar results in both mental and physical cases. Conclusions: With these outcomes, the effectiveness of a differential approach is questioned, and the relevance of a bidirectional dialog on work ability and a phased RTW plan is highlighted, regardless of the absence cause. Our study also demonstrates how policymakers need to strike a balance between obligatory and permissive legislation to better involve workplaces in RTW issues. Implications for rehabilitation: Both physically and mentally sick-listed employees could benefit from a bidirectional dialog on work ability as well as from a phased RTW plan. A greater role for employers in the RTW process should be accompanied with a support for sick-listed employees, in both physical and mental sickness absence cases. Dutch and Danish RTW legislation could be improved by carefully balancing obligatory and permissive rules and regulations to involve workplaces in RTW matters.